DESAIN DAN PENGEMBANGAN MESIN PENGAHNCUR BAHAN ORGANIK MODEL PISAU PUTAR KAPASITAS 120 KG/JAM - Hermawan, Yuni; Djumhariyanto, Dwi; Badriani, Ririn Endah; Mulyadi, Santoso (Universitas Mataram, 2025)
This design to make the organic materials crusher machine which its structure can be made easy and cheap by society, and can be operated simply, moved by gasoline engine 6.5 hp own the ability can can break the permanent organic materials upon which compost. This activity divisible in 2 solution framework that is technical solution framework and solution non technical. Technical Approach: approach to society of orchard Togung by attending method/machine to processes and dissociate the materials type so that heaping sum up the deductible materials. Approach of non technical: approach to citizen by guiding and growing to develop the society awareness about its important keep cleaning environmental and sanitation. From final this activity inferential that: making of organic materials crusher machine earn the especial problems faced by group society orchard of Togung subdistrict Sempu Banyuwangi. Making of enforceable organic materials. Machine better as according to time plan which have been determined, Especial problems partner concerning materials processing with the this machine attendance expected depending to on duty deductible subdistrict Sempu hygiene and created society of self manage materials. Result from this materials processing machine in the form organic materials upon which compost of the size 2-3 cm and organic materials process become the compost used by farmer group, so that indirectly can improve the earnings of society of orchard Togung and permeating new labour.